Exploring Charades: The Benefits and Challenges of Gamifying English Learning - Ainol Mardhiah; Heny Solekhah; Helmiyadi (Universitas Serambi Mekkah, 2024)
This study investigates Charades as a gamified learning tool in English language teaching. It explores how this game improves vocabulary, listening, speaking, and writing skills at various educational levels. The study examines the benefits and challenges of Charades, emphasizing its ability to generate dynamic and engaging learning experiences. Despite its popularity, there has been little scholarly investigation into its specialized use as a gamification tool. This study addresses this need by performing a semi-systematic literature review to investigate the benefits and challenges of Charades. The findings show Charades' effectiveness in improving language skills, such as vocabulary retention and communication abilities. However, time limits and unexpected disturbances in the classroom setting are mentioned as obstacles. This study provides further implications to maximize the positive effects of Charades while overcoming these limitations in educational settings. This study underlines the need for additional empirical research and educational practices to properly exploit Charades' benefits while reducing its challenges for an enhanced and engaged learning experience.